2015
DOI: 10.1021/acs.cgd.5b00336
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of a Series of Nitrogen-Rich Energetic Cocrystals of 5,5′-Dinitro-2H,2H′-3,3′-bi-1,2,4-triazole (DNBT)

Abstract: A series of three energetic cocrystals containing 5,5′-dinitro-2H,2H′-3,3′-bi-1,2,4-triazole (DNBT) were obtained. These incorporate a class of energetic materials that has seen significant synthetic work, the azole family (tetrazoles, triazole, pyrazole, etc.), and yet have struggled to see broad application. A cocrystal was obtained with the triazole 5amino-3-nitro-1H-1,2,4-triazole (ANTA) in a stoichiometry of 2:1 (ANTA:DNBT). Two cocrystals were obtained with the pyrazoles 1H, 4H-3,6-dinitropyrazolo[4,3-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 29 publications
1
80
0
Order By: Relevance
“…Matzger et al. have also identified that the hydrogen‐bond functionality acts as an important interaction in peroxides and energetic materials . The principal binding forces in these crystals are hydrogen bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Matzger et al. have also identified that the hydrogen‐bond functionality acts as an important interaction in peroxides and energetic materials . The principal binding forces in these crystals are hydrogen bonds.…”
Section: Resultsmentioning
confidence: 99%
“…In other work, by Zhang et al [14], an energetic co-crystal of TNB/NNAP was introduced. A series of nitrogen-rich energetic co-crystals of DNBT was reported by Matzger et al [15]. Landenberger et al [16] have also synthesized some co-crystals of HMX.…”
Section: Introductionmentioning
confidence: 96%
“…[1][2][3] Recently, a novel technique, known as cocrystallization, provides an elegant method to modify the properties of energetic materials which is also practical in pharmaceutical science. [12] A series of nitrogen-rich energetic cocrystals of DNBT is reported by Matzger et al [13] Landenberger et al have modified the properties of DADP through cocrystallization. The properties of a cocrystal is typically varied from its pure components, in terms of morphology, thermal behavior, sensitivity, detonation performance and so forth.…”
Section: Introductionmentioning
confidence: 99%